2017
DOI: 10.1177/1538574417702771
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Reduction is Important for Improving Patient and Graft Survival After Ligation and Bypass Surgery for Popliteal Artery Aneurysm

Abstract: Objectives:To report outcomes following ligation and bypass (LGB) surgery for popliteal artery aneurysm (PAA) and study factors influencing patient and graft survival. Materials and Methods:A retrospective review of patients undergoing LGB surgery for PAA between September 1999 and August 2012 at a tertiary referral vascular unit was performed. Primary graft patency (PGP), primary-assisted graft patency (PAGP), and secondary graft patency (SGP) rates were calculated using survival analyses. Patient, graft aneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Vascular cross-clamps were placed above the PAA on the DSFA to cardiovascular risk reduction (blood pressure control, dietary adjustments and smoking abstinence, antiplatelet treatment, normal blood glycaemia) can prolong grafts' patency and improves patients' survival. 13 An alternative treatment option for PAA is the use of endovascular devices. A study by Cervin et al had demonstrated inferior results of endovascular devices when compared to open repair.…”
Section: Case Presentationmentioning
confidence: 99%
“…Vascular cross-clamps were placed above the PAA on the DSFA to cardiovascular risk reduction (blood pressure control, dietary adjustments and smoking abstinence, antiplatelet treatment, normal blood glycaemia) can prolong grafts' patency and improves patients' survival. 13 An alternative treatment option for PAA is the use of endovascular devices. A study by Cervin et al had demonstrated inferior results of endovascular devices when compared to open repair.…”
Section: Case Presentationmentioning
confidence: 99%